DESIGN COMPUTER-BASED APPLICATION FOR RECRUITMENT AND SELECTION EMPLOYEE AT PT. INDONUSA TELEMEDIA - Tri Pujadi (Universitas Raharja, 2011)
This report contains about one of the applications that used by PT. Indonusa Telemedia. The function of this application to facilitate the recruitment and selection process of the company employee’s candidate. The process becomes more efficient because the application can organize the employee candidate data, interview status (proceed, hire, keep, and reject), and his comments based on the interview. The benefit for the company that uses this application is that they can increase their level of efficiency, such as in time and man labor. The level of efficiency can be increase because this application can sort the employee’s candidate data as the request of the department that request addition of employee and centralizing information in one application database.